2017
DOI: 10.1021/acs.jpcc.7b07160
|View full text |Cite
|
Sign up to set email alerts
|

Role of Monomer Alkyl Chain Length in Pretilt Angle Control of Polymer-Stabilized Liquid Crystal Alignment System

Abstract: The pretilt angle of liquid crystal (LC) molecules in LC cells was manipulated by adding a mixture of two photocurable monomers, alkyl acrylate and biphenyl diacrylate, into the LCs after the UV treatment. The hexyl acrylate and octadecyl acrylate were applied to examine the alkyl chain length effect on the pretilt angle control under the condition of a fixed concentration of biphenyl diacrylate. The LC alignment was continuously adjusted from homogeneous to homeotropic alignment in the polymer-stabilized LC s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…These investigations revealed that the surface energy (contact angle of E7) was indeed varied by photo exposure. These results are promising also for liquid crystal related research because the pretilt angle 49 of the LC director (which is important for the electrooptic performance) on a surface depends on the (now photo controllable) contact angle. Moreover, n-BPS functionalized surfaces can potentially be applied straight-forwardly (for example by spin casting of high molecular weight solvents followed by photo exposure, for example through a photo mask) to fabricate surface coatings with controllable wetting properties.…”
Section: Discussionmentioning
confidence: 91%
“…These investigations revealed that the surface energy (contact angle of E7) was indeed varied by photo exposure. These results are promising also for liquid crystal related research because the pretilt angle 49 of the LC director (which is important for the electrooptic performance) on a surface depends on the (now photo controllable) contact angle. Moreover, n-BPS functionalized surfaces can potentially be applied straight-forwardly (for example by spin casting of high molecular weight solvents followed by photo exposure, for example through a photo mask) to fabricate surface coatings with controllable wetting properties.…”
Section: Discussionmentioning
confidence: 91%
“…Based on the results of inducing LC alignment properties, we observed a general trend that polymers containing higher contents of the isoeugenol side group possessed a preference for vertical alignment of LC molecules. It has been known that the high tilt angles of LCs that produce vertical aligning properties are well correlated with low surface energy values on the alignment film and/or steric repulsion between LCs and the alignment surfaces [ 85 , 86 ]. For instance, polyimide derivatives having bulky and nonpolar groups such as 4- n -octyloxyphenyloxy and pentylcyclohexylbenzene exhibited vertical aligning behavior [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] In addition, implementing various LC driving modes is important for achieving electrooptical (EO) performance according to the varying needs of customers; since the LC driving mode is controlled by the pretilt angle of the LC alignment layer, there have been many reported attempts to control it. [5][6][7][8] Accordingly, deposition of the film used as the alignment layer and an alignment treatment process to create characteristics that induce uniform LC alignment with diverse alignment states must be achieved.…”
Section: Introductionmentioning
confidence: 99%